2012
DOI: 10.1111/j.1463-1318.2011.02668.x
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life after surgery for primary advanced rectal cancer and recurrent rectal cancer: a review

Abstract: Several aspects of HRQoL are impaired for a variable time after treatment for locally advanced or recurrence of rectal cancer. Larger prospective longitudinal studies are needed to provide further information regarding the effects of this extensive surgery on quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
45
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 28 publications
(86 reference statements)
1
45
0
Order By: Relevance
“…15 Dietary and behavioral adjustments are common functional self-care strategies for managing bowel dysfunction. 13,16,17 More than half of CRC survivors report using dietary adjustments and intentional social isolation to prevent bowel accidents in public. 18 However, evidence describing the specific types of dietary and behavioral adjustments is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…15 Dietary and behavioral adjustments are common functional self-care strategies for managing bowel dysfunction. 13,16,17 More than half of CRC survivors report using dietary adjustments and intentional social isolation to prevent bowel accidents in public. 18 However, evidence describing the specific types of dietary and behavioral adjustments is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Rectal cancer is one of the most common malignancies worldwide and has a still increasing incidence and prevalence . In 10–15% of the patients, the rectal cancer is considered locally advanced . In addition, 5–10% of rectal cancer patients develop a local recurrence without metastatic disease which can still be treated with a curative intent…”
mentioning
confidence: 99%
“…Even though the importance of patient‐reported outcomes and quality of life are increasingly recognized, research on LARC or LRRC has predominantly focused on assessing local or distance control and overall survival. A recent review concluded that only seven studies evaluated the patients' health‐related quality of life (HRQOL) after treatment for LARC or LRRC . These studies reported that the HRQL in LRRC and LARC was lower compared with patients with nonadvanced disease (NAD) and normative populations .…”
mentioning
confidence: 99%
See 2 more Smart Citations